2007
DOI: 10.1016/j.immuni.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of T Cell Receptor Signaling with a Photoactivatable Agonist

Abstract: The precise timing of signals downstream of the T cell receptor (TCR) is poorly understood. To address this problem, we prepared major histocompatibility complexes containing an antigenic peptide that is biologically inert until exposed to ultraviolet (UV) light. UV irradiation of these complexes in contact with cognate T cells enabled the high-resolution temporal analysis of signaling. Phosphorylation of the LAT adaptor molecule was observed in 4 s, and diacylglycerol production and calcium flux was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
232
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(254 citation statements)
references
References 67 publications
17
232
2
3
Order By: Relevance
“…What this might be is suggested by the fact that these invasive pseudopodia would significantly increase the surface area of T cell-APC contact, at least fivefold over a "flat" interaction, thus enabling the T cell to sample much more of the possible antigens on the APC surface. T cells are very sensitive to their peptide-MHC ligands, able to detect even one molecule (32,33), and although this is sufficient for the cell to stop, more peptide-MHC agonist ligands are usually needed (3)(4)(5)(6)(7)(8)(9)(10) to make a full response (2). Interestingly, this remarkable probing activity has not been seen in fluorescence studies of T cell-APC interactions, perhaps because of a lack of resolution and/or its rapidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What this might be is suggested by the fact that these invasive pseudopodia would significantly increase the surface area of T cell-APC contact, at least fivefold over a "flat" interaction, thus enabling the T cell to sample much more of the possible antigens on the APC surface. T cells are very sensitive to their peptide-MHC ligands, able to detect even one molecule (32,33), and although this is sufficient for the cell to stop, more peptide-MHC agonist ligands are usually needed (3)(4)(5)(6)(7)(8)(9)(10) to make a full response (2). Interestingly, this remarkable probing activity has not been seen in fluorescence studies of T cell-APC interactions, perhaps because of a lack of resolution and/or its rapidity.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of this structure correlates with robust signaling, lineage commitment, and fate determination of T cells (1)(2)(3)(4)(5)(6) and the directed secretion of cytokines and/or cytotoxic molecules. There is a wholesale reorganization of the T cell's cytoskeleton, surface molecules, and organelles, and the loss of polarity regulators or guidance cues that negatively affect T-cell activation (7,8). Whereas a great deal has been learned about the dynamics of cell-surface and signaling molecules within this interface (9,10), much less is known about changes within the cell, especially in the long-lived helper T cell, namely in antigen-presenting cell (APC) interactions, which can last for 6 or more h and need continuous T-cell receptor (TCR) engagement (11).…”
mentioning
confidence: 99%
“…Current models also indicate that cluster centralization plays an important role in signal termination and that the cSMAC is a site both for TCR down-regulation yet also for amplification of weak signals (Lee et al 2003;Mossman et al 2005;Varma et al 2006;Balagopalan et al 2007;Cemerski et al 2008;Nguyen et al 2008). A recent study using a photoactivatable agonist in a lipid bilayer system has provided even greater precision in the temporal resolution of these events and demonstrated that adapters are recruited to microclusters within four seconds (Huse et al 2007).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…41 Experiments were also conducted to determine the ability of specific APLs to induce positive selection of CD4 lineage transgenic T cells. For a pigeon cytochrome C (PCC) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] peptidespecific TCR, injections of agonist peptide alone or a mixture of antagonist and agonist peptides were given to Ii, H-2M double KO mice. 42 When injected alone, agonist peptide presumably repopulated MHC molecules in the thymus and supported positive selection of the transgenic T cells that continued for up to 2 weeks.…”
Section: Repertoires For Positive Selection Of Mhc2 Restricted Tcrsmentioning
confidence: 99%
“…[50][51][52] These microclusters are dynamically formed at the periphery of the contact area where they engage antigen and initiate signaling. 53,54 Signaling molecules and kinases, such as Lck, Zap-70, LAT, SLP-76, 50,52,54 and Grb2, 55 are localized to TCR microclusters, which translocate from the periphery of the synapse to the center in an actin dependent manner where signaling is terminated, 51 although the precise function of the cSMAC remains unresolved. 56 TCR microclusters form continuously, thus providing a signaling microclusters containing TCR, CD4 and CD8 that may recognize many self-peptide-MHC complexes.…”
Section: Tcr Microclustersmentioning
confidence: 99%